The Impact of Female Participation in Top Management on Corporate Reputation in Ghana - Safo, Jochebed Yaa (UniMAC - GIJ, 2020)
Marginalization of females is a global phenomenon that infests the various corporate societies. The quest to consciously multiply the presence of females in work space is not only for reasons of acknowledgement or justice, but also to ensure that corporations become extra receptive in terms of females’ inclusion in Ghana. In spite of the fact that more employment of females in top management provoke many conflicts and loyalties, this paper seeks to strengthen the efforts of women in the workspace. This paper explores the impact of female participation in top management and how it enhances corporate repute in the several organizations existing in Ghana
THESIS